Terramechanics-based investigation of grouser shape for rigid wheels: Comparison between rectangular and trapezoidal grousers. Issue 1 (1st January 2020) - Suzuki, Hirotaka; Watanabe, Yutaro; Kobayashi, Taizo; Iagnemma, Karl; Ozaki, Shingo
Abstract: It is important to further improve the traveling performances of the moon/planetary exploration rovers. To achieve this, we investigated the grouser shape of rigid wheels for use in such rovers, focusing particularly on rectangular and trapezoidal grousers. First, simple intrusion tests were carried out using the discrete element method. Grousers having a trapezoidal cross-sectional shape exerted a "packing effect" through which particles between grousers were strongly compressed. Next, single-wheel experiments were conducted, and the results show that sinkage was suppressed by the trapezoidal-shaped grousers. In addition, it was confirmed that trapezoidal-shaped grousers exhibited a drawbar-pull equivalent to that generated by the widely used rectangular-shaped grousers. Furthermore, we performed theoretical analysis using the resistive force theory to clarify the packing effect, and the results indicate that the use of a wheel with a trapezoidal-shaped grouser could be an effective method to improve the traveling performance of a rigid wheel.